The Genotype of Human Papilloma Virus of Male Patient with Anogenital Warts - Murtiastutik, Dwi; Mastutik, Gondo; Rahniayu, Alphania; Arista, Afria; Setyaningrum, Trisniartami (Folia Medica Indonesiana, 2019)
Human papillomavirus (HPV) infection is one of the most common sexually transmitted infections. HPV high risk (HPVHR) were HPV16,18 related with invasive penile carcinomas, and HPV low risk (HPVLR) were HPV6,11 related to anogenital warts. Male infection is usually asymptomatic that it would be explain increasing the incidence of HPV associated cancers. Identification HPV genotype is very important for predicting the development of the diseases, to be benign or malignant cancer. The objective of this study was to identify the genotype of HPV that infect men with anogential warts. This research used 12 biopsy specimens from men patient with anogenital warts at Outpatient clinic of Department Dermatology and Venereology, Dr. Soetomo General Hospital period 2016-2017. The specimens were diagnozed by pathologist and HPV gentoyping was done to detect 40 HPV genotype including HPVHR and HPVLR. The result showed that 58% (7/12) were positive for HPVLR and 42% (5/12) were positive for HPV LR/HR. The genotype HPV that infected men patient with anogenital warts is HPVLR (HPV6,11) and HPVHR (HPV18,51,52,82) with single infection of HPVLR or mutiple infection HPVLR/LR or HPVLR/HR. The infection of HPVHR would be develops to be malignant transformation. It suggested that HPV genotype needs to be checked the for the anogenital warts cases for predicting the development of the diseases.